A Dynamic Analysis Method for Complex Cable Systems Based on Dynamic Stiffness Method - Danhui Dan; Xia Liao; Fei Han (预应力技术)
Cable structure is an important type of structural bearing system. With the increasing of span and height of modern engineering structure, the length of cable used in civil engineering is increasing, and its structural form becomes more and more complex. In this case, the dynamic analysis of cable structure has become the key to the structural design, service performance monitoring and maintenance, and vibration control. The existing cable dynamic analysis theory can only consider the influence of some design parameters, or be suitable for cable systems with relatively simple structural forms, and difficult to balance analysis efficiency and accuracy and apply to the exact dynamic analysis of complex cable structures. Based on the dynamic stiffness method (DSM), this paper develops a set of exact dynamic analysis method for complex cable system; The effectiveness and applicability of this method are illustrated by taking naked cable system, composite cable system and multi-segment cable system with lateral supports as representatives. The main contributions and achievements are as follows: The exact solution of the frequency equation of small sagged cable considering bending stiffness, internal damping and additional cable force is presented; The dynamic modeling and solution of stay cables with double-sheathing anticorrosion system are given, and the influence of filling material on damping and frequency of the system is explored; Based on the DSM, the dynamic model of multi-segment cable system is established, and the corresponding dynamic solution scheme is proposed. According to this, the dynamic characteristics of the main cable of a suspension bridge are analyzed. The theoretical analysis results are in good agreement with the measured values and finite element solutions, which shows the accuracy of the proposed method. The cable dynamic analysis method proposed in this paper has high calculation accuracy and is easy to implement, which can provide theoretical basis for the initial design and health monitoring of cable and cable structures in engineering.